Antihypertensive effect of fractions derived from aqueous extract of syzygium polyanthum on anaesthetized spontaneously hypertensive rats - Abd Rahim, Erlena Nor Asmira; Ismail, Azlini; Omar, Muhammad Nor; Wan Ahmad, Wan Amir Nizam (School of Health Sciences, Universiti Sains Malaysia, 2018)
Introduction: Syzygium polyanthum leaf has been used traditionally for treating hypertension. Aqueous extract of S. polyanthum leaf (ASP) has antihypertensive effect; however, there is no further evaluation on its fractions yet. Aim: This study aims to identify the most promising fraction derived from ASP in terms of antihypertensive effect. Material and Methodology: Dried leaves of S. polyanthum were extracted using ultrasound-assisted extraction method to produce ASP and then it was fractionated using column chromatography to yield F1ASP, F2ASP and F3ASP. Spontaneously Hypertensive Rats (SHR) was anesthetized with sodium pentobarbital (50 mg/kg, i.p.), followed by left jugular vein cannulation for extract administration. Right carotid artery was then cannulated and connected to BIOPAC Blood Pressure System Version 3.6.7 for recordings of mean arterial pressure (MAP), systolic blood pressure (SBP), diastolic blood pressure (DBP) and heart rate (HR). One-way and two-way ANOVA with Sidak post-hoc tests were performed using GraphPad Prism Version 6.0. Results: F1ASP (30 to 60 mg/kg), F2ASP (20 to 60 mg/kg) and F3ASP (30 to 40 mg/kg) showed significant antihypertensive effect in comparison to negative control (normal saline). F2ASP caused more reduction (P<0.05) in MAP of SHR as compared to ASP at doses of 20 and 30 mg/kg. The antihypertensive effect by F2ASP at doses of 20 to 60 mg/kg was comparable to positive control drug, captopril at 5 mg/kg. No significant effect observed on HR. Conclusion: F2ASP has the most promising antihypertensive effect in comparison to F1ASP and F3ASP.